2003
DOI: 10.3136/fstr.9.276
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dabsyl-Cl Derivated Amino Acids by High Performance Liquid Chromatography and Tandem Mass Spectrometry

Abstract: The results showed better identification of the dabsyl-AA and the method is, therefore, more reliable in analyzing amino acid contents in complex food mediums.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…However, neither [dabsyl-Tau + 2H] 2+ (m/z 207) nor [dabsyl 2 -Tau + 2H] 2+ (m/z 351) were found. This result clearly suggested that the dabsyl-Tau was the major product of dabsyl-Cl derivatised taurine, which was similar to that of our previous analysis on amino acids when each dabsyl-Cl derivatised amino acid showed an m/z value 287 greater than that of the corresponding amino acid (Chen et al, 2003). The extra 287 value suggests that only one dabsyl group will react with one amino acid molecule, and so did the same result in this study with taurine.…”
Section: Selected Reaction Monitoring Of the Dabsyl-cl Derivativessupporting
confidence: 88%
See 3 more Smart Citations
“…However, neither [dabsyl-Tau + 2H] 2+ (m/z 207) nor [dabsyl 2 -Tau + 2H] 2+ (m/z 351) were found. This result clearly suggested that the dabsyl-Tau was the major product of dabsyl-Cl derivatised taurine, which was similar to that of our previous analysis on amino acids when each dabsyl-Cl derivatised amino acid showed an m/z value 287 greater than that of the corresponding amino acid (Chen et al, 2003). The extra 287 value suggests that only one dabsyl group will react with one amino acid molecule, and so did the same result in this study with taurine.…”
Section: Selected Reaction Monitoring Of the Dabsyl-cl Derivativessupporting
confidence: 88%
“…Therefore, Soga & Heiger (2000) developed a capillary electrophoresis electrospray ionisation mass spectrometry (CE-ESI-MS) to take advantage the efficient resolution of CE and the high selectivity and sensitivity of MS. HPLC-MS has poor resolution because of the limitation of the mobile phase, but has worked well with some of the derivatised amino acids (van Leuken et al, 1995;Liu et al, 1995;Fujii et al, 1998). We had proved the HPLC-MS/MS to be a sensitive and reliable method in the analysis of dabsyl-Cl derivatised amino acids in a complex medium (Chen et al, 2003). In this study, we are extending the HPLC-MS/MS to the analysis of anserine, carnosine and taurine in chicken essences.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…An HPLC system, modified from Chen et al. , was consisted of a reverse phase 5 μ m Symmetry (4.6 × 250 mm) column (Waters, Milford, MA, USA) connected with an HP 1100 Agilent HPLC, and equipped with an HP1046A Agilent fluorescence detector (Agilent Technologies, Palo Alto, CA, USA). A mixture of acetonitrile: 50 m m Na 2 HPO 4 /H 3 PO 4 buffer pH 4.5 (15:85) was used as mobile phase.…”
Section: Methodsmentioning
confidence: 99%